Pengukuran Kinerja Supply Chain Dengan Pendekatan Supply Chain Operation References (SCOR) - Wahyuniardi, Rizki; Syarwani, Moh.; Anggani, Ryan (Universitas Muhammadiyah Surakarta, 2017)
PT. Brodo Ganesha Indonesia is a national company engaged in manufacturing with the production of leather shoes. The company has many stakeholders and it is difficult to manage its supply chain, thereby affecting the effectiveness and efficiency of the companys supply chains. The research was conducted to measure the performance of supply chain by using Supply Chain Operation References (SCOR) approach. The initial hierarchy model of performance measurement is tailored to the companys condition to measure its supply chain performance, while the normalization of Snorm De Boer serves to equalize the value of the matrix used as the measurement indicator. The level of importance of performance attributes is measured by weighting with subjective questionnaires. Value of performance attribute obtained reliability 19,74, responsiveness 16,91, agility 11,00; and asset management 12.26. The total performance score of 59.90. This value indicates that the performance of the supply chain is in an average position.